Using social media to enhance knowledge sharing in authentic contexts : a case of undergraduate computer science students at Bindura University - Mukabeta, Tarirayi (School of Education, 2016)
Social Media(SM) is one of the major ways that the 21st Century students communicate and interact with one another. This has been evidenced by wide academic research on SM usage in modern education settings. Facebook is one of the most popular SM sites visited by students on a daily basis. In this minor-dissertation, a study of Bindura University Computer Science students' educational uses of Facebook during Industrial Attachment is explored. Qualitative results of students' interaction on Facebook (FB) to explore authentic learning during industrial attachment are discussed. In this study, conversation analysis of Facebook posts was performed against nine elements of authentic learning by Herrington Reeves and Oliver (2010). This was done to investigate the extent to which FB supported authentic learning during Industrial Attachment programme. Students were exposed to an environment where ideas could be explored at length in the context of real situations. Experiences shared and analysed showed that tasks assigned were complex and broad enough for students to actually make decisions about how they are supposed to complete them. This qualified authentic learning during industrial attachment.